PWE-106 Is functional sarcopenia associated with hepatic encephalopathy and severity of cirrhosis?. (22nd June 2015) - Clark, K; Mudrak, D; Sergent, H; Cross, T
Abstract : Introduction: The original Child-Turcotte score to assess stage severity of cirrhosis included an assessment of nutritional status. Loss of muscle mass (sarcopaenia) is increasingly recognised in patients with end-stage liver disease (ESLD) and skeletal muscle is recognised as a source of ammonia metabolism. The aim was to determine if there was an association with functional sarcopaenia, MELD score, hepatic encephalopathy (HE) and risk of death. Method: A pilot retrospective-prospective cohort analysis of inpatients with ESLD presenting at the Royal Liverpool Hospital Between January 2014–June 2014. Patients with cirrhosis had a nutritional assessment including: BMI, hand-grip strength (HGS), biochemical assessment, MELD calculation and clinical assessment for HE. End points were to assess if there was an association with HGS with liver cirrhosis severity (MELD), HE, and death. Follow-up was completed January 2015. Results: 64 patients were included in the final analysis. Male 39 (61%), median age 54 (IQR47–61 yrs). Disease aetiology was: ALD 56 (87.5%), NASH 3 (4.7%), HCV 3 (4.7%), HFE 1 (1.6%), AIH 1 (1.6%). 12 patients (19%) had HE. There were 12 deaths over the study period (19%). There was no association with HE and death on fishers exact test (p=NS). On univariate analysis the following factors were assessed for risk of death: MELD p = 0.002, Vitamin D p = 0.6, HGS p = 0, 16, age p = 0.21. There was a correlation between hand grip strength and MELD (spearmans test 0=0.04), and there was also a correlation between HGS strength and HE (spearmans p = 0.03). Conclusion: There is a correlation with HGS with liver disease severity and HE. No association was proven with HGS and survival in this small pilot study. HGS could be used to refine prognosis in ESLD. Large studies investigating the mechanisms and role of sarcopaenia in ESLD are required. Disclosure of interest: None Declared.